Analisis Putusan Nomor 467/K/AG/2017 Tentang Pembatalan Hibah Dari Orang Tua Terhadap Anak Perspektif Maṣlaḥah Mursâlah - Rasyid Siddiq; Dhiauddin Tanjung (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This research aims to examine more deeply the cancellation of gifts made by parents to their children, as regulated in Article 212 of the Compilation of Islamic Law, where gifts cannot be withdrawn, except for gifts from parents to their children. This research uses a study of decision number 467/K/AG/2017 to see whether the panel of judges applies article 212 of the Islamic law compilation to apply the rules of Ushul. This research is qualitative research with a normative juridical approach. The results of this research show that the panel of judges attempted to prioritize the benefit in accordance with the Maṣlaḥah concept put forward by Al-Ghazâlî, both at the Al-darûrât, al-hâjat and al-tahsinî levels, but the panel of judges did not directly quote the rules of ushul and prioritized the rules with a different orientation but with the aim of fulfilling the benefit of the parties involved in the lawsuit, both at the level of preserving offspring (Hifz al-Nasl) and preserving property (Hifz al-Mal) in accordance with the objectives of the syara' (maqāṣid al-syarīah).